The Potential of Dark Septate Endophyte Fungi as a Biological Control of Teak Leaf Blight Pathogen in Vitro - Firmansyah, Muhammad Alam; Surono; Sagita, Wulan Fitri; Muhammad Alam Firmansyah; Wulan Fitri Sagita (Journal of Tropical Silviculture, 2024)
Leaf blight that attacks teak (Tectona grandis L.f.) can reduce the plant's productivity. Leaf blight control can be done through dark septate endophyte (DSE). This study aims to test the ability of DSE GS2 and DSE TM fungi to inhibit the growth of pathogen colonies that cause leaf blight in vitro. Antagonistic tests of DSE against pathogen that cause leaf blight were carried out through a modified double culture test. The results of the antagonistic test showed that DSE GS2 and DSE TM could inhibit the growth of pathogens. The best inhibition results were demonstrated in the second double culture test after DSE was grown for seven days because DSE could grow stably and produce metabolite compounds. DSE TM had the best inhibition compared to DSE GS2. The mechanism of DSE inhibition against pathogens occurs through physical contact and the production of metabolite compounds characterized by the inhibition zone around the DSE. Keywords: Biocontrol, colony, Preventive, Rhizoctonia sp.